KESESUAIAN SENTRA INDUSTRI BATIK MASARAN KABUPATEN SRAGEN SEBAGAI SENTRA INDUSTRI KREATIF KERAJINAN - Az Zahra Hemas Merdekawati; Soedwiwahjono Soedwiwahjono; Rufia Andisetyana Putri (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2016)
Regional economic growth can not be separated from the contribution of economic sectors, one of them is industrial sector. Development of information and technology change society becomes more critical creating creative and innovative human resources including in the industrial sector, known as the creative industries. On the other hand, efforts to accelerate economic growth through local economic development (LED) can be supported by the activities of industrial centers. Therefore, the application of the concept of the creative industrial centers can support the region's economic growth, especially through economic development locally owned by an area. Masaran Batik Industrial Center is one axis of the local economy in Sragen. This industrial centers has contributed greatly to the Sragen District is in employment and increase in revenue. Local economic growth of Masaran Batik Industrial Center can be increased by applying the concept of creative industries center in particular craft subsector. To that end, the purpose of this research is to find out the conformity ofMasaran Batik Industrial Center as a creative craft industrial center, as a whole and based on 14 criteriasof creative craft industrial center. The method in this study using quantitative analysis techniques, which consists of the scoring method, Analytic Hierarchy Process and the ssubstitution of equation. The results of this study stated that Masaran Batik Industrial Center included in the appropriate closer classification as a creative craft industrial center. It is caused by two criteria thataren’t included in the appropriate classification, such as accessibility and infrastructure. Therefore, these criteria need to be upgraded to fit creative craft industrial center in Masaran Batik Industrial Center